'God … or a Bad, or Mad, Man': C.S. Lewis's Argument for Christ – A Systematic Theological, Historical and Philosophical Analysis of Aut Deus Aut Malus Homo. (24th November 2010) - Brazier, P. H.
<x xml:space="preserve">Abstract</x> The proposition that Jesus was 'Bad, Mad or God' is central to C.S. Lewis's popular apologetics. It is fêted by American Evangelicals, cautiously endorsed by Roman Catholics and Protestants, but often scorned by philosophers of religion. Most, mistakenly, regard Lewis's trilemma as unique. This paper examines the roots of this proposition in a two thousand year old theological and philosophical tradition (that is, aut Deus aut malus homo), grounded in the Johannine trilemma ('unbalanced liar', or 'demonically possessed', or 'the God of Israel come amongst his people'). Jesus can only be understood in the context of the Jewish religious categories he was born into; therefore, for Lewis, Jesus is who he reveals himself to be. Jesus' self‐understanding reflects his identity, his triune salvific role; this is for Lewis, the transposed reality of divine Sonship. Reason and logic are paramount here, reflected in the structure of Lewis's argument. Lewis's trilemma is not so much a proof of God's existence, but a question, a dilemma, where each and every person must come to a decision. For all its perceived faults, its simplistic language, Lewis's trilemma still is a very successful piece of Christian apologetic, grounded in a serious philosophical and theological tradition.